School Effectiveness : Supporting Student Success Through Emotional Literacy. - Tew, Marilyn (Lucky Duck Books., 2007)
Based on research in British secondary schools Marilyn Tew investigated what young people felt about school life particularly in relation to the ability to do well. The most startling finding was that the primary focus of young people in relation to being successful in school, was personal and social rather than academic.